Correlation of the hybrid layer thickness and resin tags length with the bond strength of a self-etching adhesive system. - Oliveira, Fernanda Garcia de [UNESP]; Anchieta, Rodolfo Bruniera [UNESP]; Rahal, Vanessa [UNESP]; Alexandre, Rodrigo Sversut de; Machado, Lucas Silveira [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP]; Giannini, Marcelo; Sundfeld, Renato Herman [UNESP] (My University, 2009)
The objective of this study was to measure the thickness of the hybrid layer (HLT), length of resin tags (RTL) and bond strength (BS) in the same teeth, using a self-etching adhesive system Adper Prompt L Pop to intact dentin and to analyze the correlation between HLTand RTL and their BS. Ten human molars were used for the restorative procedures and each restored tooth was sectioned in mesio-distal direction. One section was submitted to light microscopy analysis of HLT and RTL (400x). Another section was prepared and submitted to the microtensile bond test (0.5 mm/min). The fractured surfaces were analyzed using scanning electron microscopy to determine the failure pattern. Correlation between HLT and RTL with the BS data was analyzed by linear regression. The mean values of HLT, RTL and BS were 3.36 microm, 12.97 microm and 14.10 MPa, respectively. No significant relationship between BS and HLT (R2= 0.011, p>0.05) and between BS and RTL (R2= 0.038) was observed. The results suggested that there was no significant correlation between the HLT and RTL with the BS of the self-etching adhesive to dentin.
Keywords: resin; dental bonding; dental etching; human; in vitro study; materials testing; Dental Bonding; Dental Etching; Humans; Materials Testing; Resins, Synthetic